PENGARUH SENAM PROLANIS TERHADAP PERUBAHAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE II - Armen Patria; Budi Antoro; Nova Nurwinda Sari; Novika Andora (Jurnal Riset Media Keperawatan, 2023)
Prolanis gymnastics is a new program from the government with the aim of one of which is to control blood sugar in DM II patients, so many people do not know about it, even most of the people who already know but are less compliant in participating in the Prolanis program and as health workers have an obligation to socialize and activators in activities. This type of quantitative research design is a Quasi Experiment with a one group pre test and post test design approach. The population in this study were diabetes mellitus patients in the working area of ​​the Seputih Banyak Health Center, Central Lampung Regency, as of January - March 2020, totaling 48 people with a total sample of 48 people. In this study the sampling technique used was the total population. In this study, the paired T test was used. Based on statistical tests, it is known that the p-value is 0.000 or p-value <0.05, which means that there is an effect of Prolanis Exercise on Changes in Blood Sugar Levels in Diabetes Mellitus Patients in the Working Area of ​​the Seputih Banyak Health Center, Central Lampung Regency in 2020, it is hoped that this will increase family insight and knowledge about how to improve hemodynamic conditions in diabetic patients and as a basis for providing information to reduce the percentage of people with diabetes